Electrochemical skin conductance by Sudoscan®: a new tool to predict intradialytic hypotension. Issue 8 (22nd May 2021) - Reach, Pauline; Touzot, Maxime; Lombardi, Yannis; Maheas, Catherine; Sacco, Emmanuelle; Fels, Audrey; Beaussier, Hélène; Ureña-Torres, Pablo; Chatellier, Gilles; Ridel, Christophe; Zuber, Mathieu
Abstract: Background: Intradialytic hypotension (IDH), a common complication in haemodialysis (HD) patients, is associated with multiple risk factors including cardiac dysfunction and alterations of the peripheral autonomic nervous system. To what extent dysautonomia may contribute to the occurrence of IDH remains elusive. We sought to investigate the clinical utility of Sudocan ®, a device that quantifies dysautonomia, in the prediction of IDH. Methods: We conducted a prospective monocentric study in adult HD patients from July 2019 to February 2020. Dysautonomia was assessed by the measurements of hand and foot electrochemical skin conductance (ESC) using Sudocan ®, before HD. The primary endpoint was the incidence of IDH (The National Kidney Foundation/Kidney-Dialysis Outcome Quality Initiative definition), according to the presence of a pathological hand and/or foot ESC value, during the 3-month study period. Results: A total of 176 HD patients (64 ± 14 years old) were enrolled. Mean pre-dialysis HD hand and foot ESC was 45 ± 20 and 54 ± 22 µS, respectively. About 35% and 40% of patients had a pathological ESC at the hand and foot, respectively. IDH occurred in 46 patients. Logistic regression showed that pathologic pre-dialysis HD hand ESC was associated with an increased risk of IDH [odds ratio = 2.56, 95% CI (1.04–6.67), P = 0.04]. The cumulative risk incidence of IHD during the study was 5.65 [95% CI (2.04–15.71), P = 0.001] and 3.71 [95% CI (1.41–9.76), P = 0.008], with a pathological hand and foot ESC, respectively. Conclusions: A pathological hand ESC, as assessed by a non-invasive Sudoscan ® test, is associated with an increased risk of IDH. Graphical Abstract: